Arbitration as a dispute resolution method for B2C property development contracts - A comparative study on consumer arbitration in Brazil and Germany - Salomão, Deborah Alcici; Justus Liebig University Giessen (My University, 2019)
All things considered, access to justice for consumers, through either arbitration or courts, only occurs if on ponders the underprivileged position of the consumer in relation to the developer. The disparity of balance in the B2C legal relationship is substantial in standard property development contracts. First, because the bargaining position of the consumer in a standard contract is in most cases inexistent. Second, because a property development contract has a major importance for the consumer. It means the purchase of a dream, releasing the consumer from the rent and normally a safe investment of money. Hence, consumer protection is important to compensate this unbalanced relationship even in the procedural phase.Yet, consumer protection should not be an end in itself. One should not detach consumer protection from the legal and economic reality. It is very important to protect the consumer only as long as they need protection, avoiding exaggerate state intervention into the consumer´s private autonomy. Protection of consumers must not mean to ban consumer arbitration, depriving them from the advantages of this dispute resolution method. One should not be afraid of the ADR tendencies in the consumerist field, on the contrary, the Law should enable appropriate arbitration for consumers, especially if it is known that some kinds of disputes, like property development cases, can profit from them.The core of the consumer protection is the principle of equality. It means to treat the equals equally and the unequals unequally, in the measure of their inequality. In this sense, the law must treat the consumer and the company unequally in arbitration, since they have different experience, expertise, knowledge, information and bargaining position. This disadvantageous position of the consumer can and should be balanced by creating a filter to arbitration clauses that considers the intention of the consumer to arbitrate, after the dispute arises and by creating an especial system for B2C construction arbitration, with tailor-made rules.Therefore, the development of practical arbitration solutions for consumers with property development disputes represents a great advance in both consumer law and arbitration law, for it gives the consumer one more way to access justice.In essence, the legal community, the traders, the consumers and even the states all over the world have been in the process of acknowledging the benefits of ADR for consumer disputes, thereunder also arbitration. Eventually Brazil and Germany will also probably face the challenge of offering adequate arbitration for consumer disputes. This thesis hopes to contribute for a fruitful debate about the possibilities to make it happen. May the ADR wave in consumer law be called a tendency or even a trend, it is not time to swim against the current, it is time to make this new path viable.
Keywords: ddc:340